The Philippine national development plan : directions for the 21st century. (Manila, Philippines : The Republic, 1998)
Our development vision for the21st century is to create a modern and human society, raise the quality of life of all Filipinos-children, youth, women, and men alike -and bequeath this society in ecological healthy state to future generations.
Part I. Sources of long-run economic growth and equitable development -- Part II. Modernization strategies -- Part III. Foundations for stability and long-term growth.
Keywords: ECONOMIC POLICY